Pendidikan Remaja Dalam Perspektif Psikologi Pendidikan dan Peran Guru Bimbingan Konseling - Fauziah Nasution; Mutia Adella; Ichsani Walidaini; Mahyuni Harahap; Lisna Marselina (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Each phase of age that the human being undergoes has special characteristics that distinguish it from other phases of growth. The purpose of this study was to find out how influential psychology education is on adolescent education. This research uses qualitative research methods, namely by utilizing sources from previous research and utilizing other sources that are library analysis as the main object of research. The results of this study are the most appropriate learning model in adolescent psychology when facing various problems that relate physical, cognitive, emotional and psychosocial. It takes the role of parents, teachers and the community to recognize their world and provide opportunities to develop within their potential. Like a form of giving rules that are looser but still controlled because they are starting to be independent. Giving praise, appreciation, affection, and growing confidence in interacting with the environment. Confidence here is when a child feels he is capable and dares to be different and holds firm to his principles when what he brings is true. The role of the counseling teacher or counselor is not only focused on helping students with problems, but on assisting all students in developing a variety of potentials, including the development of learning/academic, career, personal, and social aspects. Keywords: Teenager, psychology , counselor